The Dhikir and Prayer Therapy on Reducing Blood Pressure in Hypertension Patients: Systematic Literature Review - Sopiah, Popi; Nuryani, Reni; Sukaesih, Nunung Siti; Lindasari, Sri Wulan; Assyfa, Nurul (Universitas Tribhuwana Tunggadewi, 2024)
Hypertension can lead to a variety of consequences, including death. Alternative therapies, such as Dhikr and prayer therapy, have emerged as a response to the negative effects of medications used to treat hypertension. The therapy of Dhikr and prayer worked by inhibiting sympathetic nerve dominance and activating parasympathetic nerves, resulting in a soothing effect. The goal of this paper was to conduct a literature search to determine the effectiveness of Dhikr therapy and prayer in lowering blood pressure in hypertension patients. The method involved investigating evidence published in electronic data from Google Scholar and Semantic Scholar. Using Publish or Perish, we searched for data from 2018 to 2023 using the terms